2011
DOI: 10.1001/archgenpsychiatry.2010.199
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Antipsychotic Treatment and Brain Volumes

Abstract: Context Progressive brain volume changes in schizophrenia are thought to be due principally to the disease. However, recent animal studies indicate that antipsychotics, the mainstay of treatment for schizophrenia patients, may also contribute to brain tissue volume decrement. Because antipsychotics are prescribed for long periods for schizophrenia patients and have increasingly widespread use in other psychiatric disorders, it is imperative to determine their long-term effects on the human brain. Objective T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
297
5
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 857 publications
(332 citation statements)
references
References 59 publications
17
297
5
3
Order By: Relevance
“…Notably, when we used current medication in CPZ equivalent units as a quantitative measures of antipsychotic medication (at the cost of a reduced sample size), an effect on MOFC thickness was not observed. While past studies predominantly reported volume and thickness deficits in frontal brain regions in patients treated with typical compared with those treated with atypical antipsychotics or unmedicated patients (van Haren et al 2011;Lesh et al 2015;Vita et al 2015), there have also been many conflicting findings (Cahn et al 2002;Ho et al 2011). Attempting to reconcile previous reports, it has been suggested that antipsychotic medication effects on brain structure might be substance specific (Xiao et al 2008) and might also depend on illness chronicity and the duration of untreated psychosis.…”
Section: Antipsychotic Medicationmentioning
confidence: 99%
“…Notably, when we used current medication in CPZ equivalent units as a quantitative measures of antipsychotic medication (at the cost of a reduced sample size), an effect on MOFC thickness was not observed. While past studies predominantly reported volume and thickness deficits in frontal brain regions in patients treated with typical compared with those treated with atypical antipsychotics or unmedicated patients (van Haren et al 2011;Lesh et al 2015;Vita et al 2015), there have also been many conflicting findings (Cahn et al 2002;Ho et al 2011). Attempting to reconcile previous reports, it has been suggested that antipsychotic medication effects on brain structure might be substance specific (Xiao et al 2008) and might also depend on illness chronicity and the duration of untreated psychosis.…”
Section: Antipsychotic Medicationmentioning
confidence: 99%
“…In addition, widespread cortical thinning of the cerebral cortex involving not just frontotemporal regions but also parietal and occipital regions has been demonstrated in individuals with schizophrenia compared with healthy controls (Nesvåg et al, 2008;Sprooten et al, 2013). It remains unclear whether these progressive changes are inherent to the pathophysiological disease processes underlying schizophrenia or whether they are related to or are accelerated by treatment with antipsychotic agents or other illness-related factors (Ho et al, 2011;Zipursky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ho, Andreasen, Ziebell, Pierson, and Magnotta (2011) recently published the results of their 14 year study in which they used images of the brains of first episode psychotic patients treated with antipsychotic (anti-dopaminergic) drugs over time (average of 7 years). They documented a notable "brain tissue volume decrement" associated with both atypical antipsychotics (quetiapine, risperidone, aripiprazole, olanzapine, clozapine, ziprasidone) and traditional neuroleptics (old drugs such as chlorpromazine).…”
Section: Pharmacological Downsidesmentioning
confidence: 99%
“…These growth factors are vital for the health of the brain (Schwartz & Schechter, 2011;Swartz & Ziv, 2008). In reviewing the data, Ho et al (2011) acknowledged that a cost/benefit analysis might justify the use of antipsychotics for treating schizophrenia but they questioned the use of antipsychotics in mood disorders.…”
Section: Pharmacological Downsidesmentioning
confidence: 99%
See 1 more Smart Citation